Análise de recuo de falésias no litoral do Estado do Rio Grande do Norte - Câmara, Michel Rodrigues (2018)
On the Coast of the State of Rio Grande do Norte, Northeastern Brazil, coastal erosion generates several problems, especially in the municipality of Tibau do Sul, where the tourist movement and the intense real estate speculation cause several environmental conflicts. Geoprocessing techniques were utilized through Digital Image Processing and Geographic Information System in the multitemporal analysis through the DSAS (Digital Shoreline Analysis System) tool in a scale of 3 decades, using images of remote sensors of spatial resolution of 30 meters and 5 meters to identify the areas that had erosive retreat of cliffs in the coast of the State of Rio Grande do Norte, measuring the retreat and the characterization of these environments. Five areas with erosive retreats were highlighted in cliffs of up to 101.1 meters, putting at risk areas of heavy urban occupation, diverse infrastructures and access roads. Then, using the same method, a 1-year multitemporal analysis was performed using remote sensing images of 1-meter spatial resolution in the city of Tibau do Sul, identifying stretches that obtained erosive retreat of up to 1.99 meters. Later, for the identification and characterization of the erosive processes in the study area, the checklist adapted to the coastal features in the research area was used, that is, coast with cliffs elaborated by Braga (2005). Finally, a comparison was made of the information obtained in the checklist of the same author in his field visit in 2004 with the data obtained in the checklist at the present time, identifying the areas that are still in continuous process of coastal and / or pluvial erosion as the areas in which a balance in the dynamics was identified, remaining stable. In addition to other stretches that formerly presented only one type of main erosion and currently two major types of erosion. It was verified that the checklist is an adequate tool in the identification of coastal erosive processes and pluvial, organizing in an organized way the collection and analysis of the information regarding the area of action and characteristics that trigger coastal and rain erosion. Such information serves as a subsidy for coastal management in these coastal environments of the Rio Grande do Norte coast.